Improving Learning Activities and Outcomes Using the Inquiry Learning Model and Number Head Together - Iswatun Hasanah; Ike Hananik (Journal of Social Research, 2025)
The background of this research was conducted because of the lack of activity and student learning outcomes. This is caused by the application of learning models that are less varied and mostly still emphasized on teachers making student less enthusiastic in learning activities and the lack of collaboration between student during learning reduces meaningful learning and student activity, so that it becomes a problem and an obstacle in classroom learning, plus the lack of scientific way of thinking and understanding in the concept of a learning material. Based on these problems, the research method used was Classroom Action Research in 2 meetings using the Inquiry Learning and Number Head Together Models. Data analysis was carried out by means of qualitative and quantitative. The results showed that teacher activity with a proportions of 78% in the first meeting became 89% at the final meeting with very good criteria. Student activity with the proportion of of 40% in the first meeting became 80% at the final meeting achieves active criteria. Learning outcomes with a proportions of 70% in the first meeting become 90% in the final meeting. Overall these results show a good improvement.